Analysis, Evaluation and Comparison of Religious Tourism with Ecotourism: Case Studies in Armenia and Tanzania - Varani, Nicoletta; Mamayusupova, Kristina (Eco-Tourism and Sustainable Development, 2025)
This contribution is the result of an experience of two recent trips —“the field study” — , to Armenia and Tanzania, carried out separately by the two authors with the aim of exploring particular aspects of sustainable tourism through the analysis, interpretation and comparison of religious tourism with ecotourism in both countries. The application of these two types of tourism in the form of sustainable tourism practices aims to enhance and protect the territories under consideration and contribute to their local and regional economic development. The methodology employed in the comparative analysis is based on the investigation of political strategies, official statistics, national and regional documentation adopted by Armenia and Tanzania in relation to the tourism practices adopted, and participant observation. Tourism practices in Armenia and Tanzania in recent times have shown a focus on sustainability, aimed at developing these countries and preserving their territories and cultural heritage, as well as increasing tourists' awareness of their positive impact on the territories they visit. Acting on religious tourism in synergy with ecotourism helps tourists reduce their ecological impact, contribute to the conservation of cultural landscapes, and broaden their spiritual experiences. Traveling responsibly, sustainably, and ecospiritually through sacred sites and natural landscapes, in line with political strategies aimed at the sustainability of a country visited, increases tourism awareness of the benefits they bring to the local community and the heritage they bring. The spread of ecospiritual practices practiced in sustainable tourist travel also leads to increased heritage sustainability.